BEŞİR GÖĞÜŞ'ÜN TÜRKÇE EĞİTİMİ İLE İLGİLİ ESERLERİ VE TÜRKÇE ANLAYIŞI ÜZERİNE BİR İNCELEME - TUNÇ, FATMA (Fırat Üniveristesi, 2009)
Dil, sürekli olarak değişen ve gelişen aynı zamanda toplumlar arası iletişimi sağlayan önemli bir varlıktır. Dilin bir diğer ortak özelliği de kültür taşımasıdır. Toplumsal gelişmenin gereği kültürün korunması ve gelecek nesillere aktarılmasında büyük öneme sahiptir.Toplumsal gelişmenin önemli araçlarından olan ana dili eğitimi alanında yetkin birisim olan Beşir Göğüş, üzerinde durulması gereken isimlerden birisidir. Bir ana dili eğitimcisi olan Beşir Göğüş, dilin etkin olarak kullanılması ve bu aracın doğru, bilinçli bir şekilde öğretilmesi için çaba harcamış bir eğitimcidir. Ana dili bireyin hayatında öğrenmiş olduğu ilk dildir. Bu nedenle birey dünyaya geldiği ilk andan itibaren ailesinden veya çevresinden ana dilini öğrenmeye başlar. Çevresindeki varlıkları ilk duyduğu dille adlandırır. Çocuk; soyut, somut kavramları, iyilik ve kötülük, sevgi, saygı gibi kavramları öğrenmiş olduğu dille şekillendirir. Göğüş'e göre ana dili öğretimi küçük yaşlarda ve doğal ortamlarda gerçekleştirilmesi gereken bir beceridir. Çocuk dilin kurallarını ezbere bir şekilde değil, doğal ortamda konuşarak, anlayarak öğrenmeye çalışır. Okulda ise planlı, programlı bir öğretim cetveli çerçevesinde gerçekleştirir. Ancak okul çevresinde gerçekleştirilen eğitim sadece okuma ve anlatmayla sınırlı kalıp; kısır bir döngüde kalmamalıdır. Çocuk ana dilini birebir yaşayarak; yazarak, konuşarak ve anlatarak öğrenmelidir. Yani okulda sadece kuru ezbere dil kurallarıyla sınırlı kalınmamalıdır.Bu çalışmada Türkçeye gönül vermiş ve hayatının sonuna kadar ana dili öğretimiyle bir eğitimcinin Türkçe anlayışı ve eserlerinin tanıtılmasına yer verilmiştir. Beşir Göğüş; devlet okullarında ve eğitimimizin çeşitli düzeylerinde öğretmenlik ve yöneticilik yapmış, yaşamının 30 yıldan fazlasını ulusal eğitimimizin gelişmesine harcamış, bir şahsiyettir. Yetiştirmiş olduğu öğrenciler ve eğitimcilerle ve her seviye için yazmış olduğu ders kitaplarıyla birçok kuşağın yetişmesinde pay sahibi bir dil uzmanı ve eğitimcidir.Anahtar sözcükler: Beşir Göğüş, ana dili, Türkçe eğitimi, yazın eğitimi, eğitim.

Language is an important constantly changing and developing device which enables the communication among societies. Another common characteristic of the language is that it carries the culture. The necessity of social growth has great significance in preserving the culture and transfering it to the next generations.Beşir Göğüş, who is an influential figure in the study-field of Teaching of Mother Language which is one of the important constituents of social growth, is one of those names which should be dwelt upon. Beşir Göğüş, who was a Mother Language educationalist, was one of the educationalists who strived for the efficient use of the language and for a conscious and proper teaching of this device. The Mother Language is the first language an individual learns in his life. Thus, the individual starts learning the mother language from his family or environment the moment he is born; he names everything in his environment with the language he first hears. The child forms the abstract and concrete concepts such as good and bad, love and respect with the language he has learnt. According to Göğüş, the learning of the Mother Language is a skill which should be fulfilled in early ages and in natural atmospheres. The child tries to learn the rules of the language not in a by heart fashion, but by speaking and understanding it in a natural atmosphere. Whereas, this is carried out in a planned and programmed teaching framework at school. However, the teaching that is carried out at school should not remain in a vicious circle and should not be limited to just reading and narration. The child should learn his mother language by experiencing, writing, speaking and communicating it himself. That is, the school should not be restricted to bare memorization of the language rules.This study deals with the Turkish Language concept and the introduction of the works of an educationalist who devoted himself to Turkish Language and strived for the teaching of the mother language throughout his life. Beşir Göğüş is an important figure who served in the teaching and administrative positions at state-schools and various levels of our national education, and who spent more than 30 years of his life for the development of our national education. He was a language expert and educationalist who had had a role in the growth of many generations along with the students and instructors he trained and the course books he wrote for every level of learning.Key Words: Beşir Göğüş, Mother Language, Teaching of Turkish Language, Literary Education, Education.
Firat university institute of social sciences department of Turkish language education on the works of Beşir Göğüş on Turkish language education and his concept of Turkish
Keywords: Eğitim ve Öğretim